1981
DOI: 10.1172/jci110162
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular dynamics and morphologic changes in the generalized Shwartzman reaction in postpartum rats.

Abstract: A B S T R A C T The roles of glomerular functional and morphologic changes were examined in the acute renal failure associated with generalized Shwartzman reaction in postpartum Munich Wistar rats. The susceptibility of postpartum rats to acute deterioration in renal function after a 2-h endotoxin infusion was found to be greater than in virgin litter mates: glomerular filtration rate fell by 93% in the former vs. 24% in the latter group (P < 0.001). In postpartum rats there were marked changes in platelet cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Renal effects of endotoxemia, in terms of decreased RPF and GFR, already became evident at t = 30 min. This confirms results of others [11][12][13] that renal failure is one of the earliest findings during shock: it may occur before or even without systemic changes, as we have discussed before [1], I n spite of the early acute renal failure (ARF), renal ATP concentra tion did not fall during the whole experimental period. The only early metabolic change we found was an increase in renal glucose concentration, at t = 30 min, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Renal effects of endotoxemia, in terms of decreased RPF and GFR, already became evident at t = 30 min. This confirms results of others [11][12][13] that renal failure is one of the earliest findings during shock: it may occur before or even without systemic changes, as we have discussed before [1], I n spite of the early acute renal failure (ARF), renal ATP concentra tion did not fall during the whole experimental period. The only early metabolic change we found was an increase in renal glucose concentration, at t = 30 min, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…The improved RBF observed with RAD therapy in the face of profound hypotension is noteworthy. Prior studies have suggested that the declines in RBF in response to endotoxin shock are related to vasoactive compounds and not structural vascular processes, such as microthrombi (55)(56)(57). Whether the diminished renal vascular resistance in response to cell therapy in Gram-negative septic shock is due to the release of a vasoactive moiety or is secondary to local cytokine changes requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…32 Dysfunction of sensory neurons and excess inflammatory cytokines (IL-6, tumor necrosis factor-α, IL-1β, granulocyte colony-stimulating factor) released from activated neutrophils are central themes of the mechanism responsible for the clinical manifestations of septic shock syndrome. 33,34 For a better understanding of the human adaptive response to inflammation, a number of investigators including us, have used animal models 35,36,37,38 Taken together, animal studies demonstrate that along with a complex set of changes, sepsis is associated with a decline in vascular tone, accompanied by marked regionalization of vital organ blood flow. 35,39 For example, the kidney circulation follows a biphasic pattern: first an increase followed by a decrease in renal artery blood flow.…”
Section: Discussionmentioning
confidence: 99%